Corrosion and Mechanical Behavior of Metal Materials - Liu, Ming (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Dear Colleagues,Many structural metal materials work under the coupling condition of the load and corrosion environment. Therefore, it is very necessary to study the corrosion and mechanical behavior of metal structural materials. The corrosion behaviors of metals under the coupling condition of the mechanics and corrosion environment mainly include stress corrosion cracking, hydrogen-induced cracking, corrosion fatigue, erosion corrosion, wear corrosion, etc. From the macroscopic or microscopic point of view, these corrosion damages all involve the fracture process, and fractures are caused by environmental factors, also known as environmental fractures. Thus, this Special Issue, "Corrosion and Mechanical Behavior of Metal Materials", will focus on the environmental fracture behavior of metal materials, including but not limited to experimental, computational, or theoretical studies on environmental corrosion fracture of high-strength metal materials.